Humanist reason a history, an argument, a plan - Hayot, Eric 1972- (Columbia University Press, 2021)
Ask just about any humanist, and you will hear that the humanities are in a crisis. Facing utilitarian approaches to education, the corporatization of the university, plummeting enrollments, budget cuts, and political critiques from right, left, and center, humanists find themselves on the defensive. Eric Hayot argues that it is time to make a positive case for what the humanities are and what they can become.Hayot challenges scholars and students in the humanities to rethink and reconsider the work they do. Examining the origins of the humanist ethos in nineteenth-century Germany and tracing its philosophical roots back to Immanuel Kant, Hayot returns to the history of justifications for the humanities in order to build the groundwork for their future development. He develops the concept of "humanist reason" to understand the nature of humanist intellectual work and lays out a series of principles that undergird this core idea. Together, they constitute a provocative intellectual and practical program for a new way of thinking about the humanities, humanist thought, and their role in the university and beyond. Rather than appealing to familiar ethical or moral rationales for the importance of the humanities, Humanist Reason lays out a new vision that moves beyond traditional disciplines to demonstrate what the humanities can tell us about our world